Assessing Physical Activity Levels of Elderly Malays Living in Semi-Rural Areas Using Tri-Axial Accelerometer. - Nurdiana A.; C. M., Ahmad Munir; Singh, Rabindarjeet; W. J., Brown; Clark B. (Malaysian Journal of Nutrition, 2016)
Introduction: Population-based physical activity (PA) data are lacking in multicultural South East Asia. Malaysian elderly Malays, for example, are occupied daily with religious and community activities. Those living in rural areas also have a distinctively different lifestyle in terms of walking habits and leisure-time activities, compared to people from urban areas. Methods: A cross-sectional study was conducted with 146 community-dwelling Malay adults aged 60 to 85 years (mean (SD) = 67.6 (6.4) years) living in semi-rural areas in Seberang Perai Utara, Penang, Malaysia. Each participant was interviewed using a questionnaire for their socio-economic background and self-reported PA levels. Then, the participants were invited to wear an accelerometer (ActiGraph GT3X or GT3X+) during their waking hours for seven consecutive days. Results: Daily activity patterns of the participants were dominated by sedentary time (7.9 (SD 2.1) hours/day; 52% of wear time) and light intensity activity (7.0 (1.9) hours/day; 46% of wear time). The participants spent 24 (SD 30) minutes daily in ‘health enhancing’ (i.e. moderatevigorous intensity) activities. Men spent significantly more time in higher intensity acti-vities than women. Average daily step count was more than 10,000 (mean = 12,542 [4,857]) steps/day. Conclusion: Based on the accelerometer counts, these elderly Malay participants were assessed to be sedentary for most of the time during the day, though their daily step count exceeded 10,000 on average. Community- living older adults, especially women,should be encouraged to increase their physical activity levels.